The Role of Public Administration in Disaster Risk Management (A Study on The Responsiveness of Banjarnegara Regency Local Government to Natural Disasters in 2025) - Stevy Bastiani Najoan; Lucyana Steyfany Angwirawan; Dinda Ayuni Faddila; Irkab Ala Firdausy (Yayasan Riset dan Pengembangan Intelektual, 2025)
Disaster management is an integral part of public administration functions in ensuring the safety and welfare of society. This article aims to analyze the role of public administration in disaster risk management, focusing on the responsiveness of local governments in addressing natural disasters in 2025. The study employs a qualitative approach with a case study method in Banjarnegara Regency, one of the disaster-prone areas in Indonesia. Data were collected through in-depth interviews, documentation, and field observations involving local government agencies directly engaged in disaster response. The findings reveal that public administration plays a crucial role in three key aspects: mitigation, preparedness, and emergency response. The local government demonstrated a rapid response in aid distribution and inter-agency coordination, although challenges remain in terms of human resource capacity and disaster information systems. The article recommends strengthening institutional capacity, optimizing information technology, and enhancing community participation as strategic steps toward more effective and sustainable disaster risk governance.